High-resolution crossover mapping reveals similarities and differences of male and female recombination in maize - Penny M. A. Kianian (Nature Portfolio, 2018)
Sex-specific meiotic crossover (CO) landscapes have been identified in multiple species. Here, the authors show that male and female meioses in maize have similar CO landscapes, and differences between COs in the two sexes only exists in their location relative to transcription start sites and some chromatin marks.